2021
DOI: 10.1039/d1re00121c
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatically excited liquid marble as a micromixer

Abstract: Liquid marble is a promising microfluidic platform for microreactor applications. However, the lack of contactless and on-demand mixing strategies significantly hinders its potential. This paper reports the use of electrostatic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 64 publications
(75 reference statements)
0
26
0
Order By: Relevance
“…External excitation that induces internal flow leading to mixing enhancement is highly desirable. 44 Applying motion to a droplet or liquid marble has long been utilised as one of the simplest methods to improve mixing since the motion generates a steady internal recirculating flow. [52][53][54][55] Song et al rolled a droplet to create chaotic advection that led to sub-millisecond mixing.…”
Section: Mixing In a Liquid Marblementioning
confidence: 99%
See 3 more Smart Citations
“…External excitation that induces internal flow leading to mixing enhancement is highly desirable. 44 Applying motion to a droplet or liquid marble has long been utilised as one of the simplest methods to improve mixing since the motion generates a steady internal recirculating flow. [52][53][54][55] Song et al rolled a droplet to create chaotic advection that led to sub-millisecond mixing.…”
Section: Mixing In a Liquid Marblementioning
confidence: 99%
“…Previous studies showed that periodic deformation substantially improves mixing performances for liquid droplets and liquid marbles. 44 Larger liquid marbles are also inherently easier to deform since the effect of surface tension diminishes with increasing volume. 44…”
Section: Deformation Of a Liquid Marblementioning
confidence: 99%
See 2 more Smart Citations
“…Besides measuring conventional liquid droplets, these tools have been used to analyse liquid marbles, which are liquid droplets coated with micro-or nanoparticles [21][22][23][24][25][26][27]. Thanks to their unique features such as high elasticity, self-propulsion, and ability to coalesce, liquid marbles are present in applications such as micro-or nanoscale chemical reaction control, microfluidics, or cosmetics [28][29][30][31][32][33][34][35][36][37][38][39][40][41]. When liquid marbles rest on a flat and smooth surface, they are analogous to a sessile droplet on a non-wetting solid surface [42].…”
Section: Introductionmentioning
confidence: 99%